2007
DOI: 10.1158/1541-7786.mcr-07-0388
|View full text |Cite
|
Sign up to set email alerts
|

Defective in Mitotic Arrest 1/Ring Finger 8 Is a Checkpoint Protein That Antagonizes the Human Mitotic Exit Network

Abstract: A molecular pathway homologous to the S. cerevisiae mitotic exit network (MEN) and S. pombe septation initiation network has recently been described in higher eukaryotes and involves the tumor suppressor kinase LATS1 and its subunit MOB1A. The yeast MEN/septation initiation network pathways are regulated by the ubiquitin ligase defective in mitotic arrest 1 (Dma1p), a checkpoint protein that helps maintain prometaphase arrest when cells are exposed to microtubule poisons. We identified here the RING domain pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 35 publications
(46 reference statements)
2
17
0
1
Order By: Relevance
“…Interestingly, the human Dma homolog Rnf8 localizes at the spindle midbody and has been proposed to antagonize the human mitotic exit network [59], suggesting that it might be the functional human counterpart of Dma proteins. The identification of the ubiquitylation targets of Dma proteins will be a challenging task for future research and will help to elucidate the mechanism(s) through which they control cytokinesis and help maintaining genome stability.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the human Dma homolog Rnf8 localizes at the spindle midbody and has been proposed to antagonize the human mitotic exit network [59], suggesting that it might be the functional human counterpart of Dma proteins. The identification of the ubiquitylation targets of Dma proteins will be a challenging task for future research and will help to elucidate the mechanism(s) through which they control cytokinesis and help maintaining genome stability.…”
Section: Discussionmentioning
confidence: 99%
“…While RNF8 functions involving UBC13-dependent K63-linked ubiquitin chains play important roles in assembling checkpoint and repair proteins at sites of DNA breaks, we did not observe a requirement for UBCH8 in these events (9) (Supplementary Figure S4C), suggesting that the RNF8–UBCH8 module may regulate yet-to-be identified cellular processes. Apart from mediating histone ubiquitylation events at DNA damage sites, previous studies indicated that RNF8 regulates mitotic exit (27,28). Thus, it will be of significant interest to test whether the RNF8-dependent K48-ubiquitin chains may be important in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Although difficult to analyze experimentally, it is possible that sequestration of such proteins into mitotic structures prevents their recruitment and/ or accumulation at sites of damaged chromatin. For instance, 53BP1 is loaded onto the kinetochore during prophase, 27 while RNF8 not only localizes to the midbody, where it regulates mitotic exit, 28,29 but is also recruited to other two mitotic structures: centrosomes and kinetochores. 23 Further analysis of RNF168 localization during mitosis revealed that, similarly to RNF8, it displayed punctate staining at kinetochores but was excluded from γH2AX foci ( Fig.…”
Section: Lack Of Dna Damage Checkpoint In Mitosis: the Art Of Prioritmentioning
confidence: 99%